The effect of composite bonding spot size and location on the performance of poly-ether-ether-ketone (PEEK) retainer wires - Ammar S Kadhum; Akram F Alhuwaizi (College of Dentistry/ University of Baghdad, 2021)
Background: Poly-ether-ether-ketone(PEEK) has been introduced to many dental fields. Recently it was tested as a retainer wire‎ following orthodontic treatment. This study aimed to investigate the effect of changing the bonding spot size and location on the performance of PEEK retainer wires. Methods: A biomechanical study involving four three-dimensional finite element models was performed. The basic model was with a 0.8 mm cylindrical cross-section PEEK wire, bonded at the center of the lingual surface of the mandibular incisors with 4 mm in diameter composite spots. Two other models were designed with 3 mm and 5 mm composite sizes. The last model was created with the composite bonding spot of the canine away from the center of the crown, closer to the lateral incisor. The linear displacement of the teeth, strains of the periodontal ligament, and stresses in PEEK wire and composite were evaluated. The data was numerically produced with color coded display by the software. Selected values were tabulated and compared among models. Results: The amount of linear displacement and strain was very low. Stresses in the wire and composite were affected by the size and position of the composite bonding spot. The safe limits were identified at 235 MPa for PEEK and 100 MPa for composite. The basic model had a von Mises stress in the PEEK wire of 122.09 MPa, and a maximum principal stress in the composite of 99.779 MPa. Both stresses were within the safe limits, which means a lower risk of failure in PEEK and composite. All other models had stresses that exceeded the safe limit of the composite. The 3 mm composite model was the only one that developed stresses in the wire more than the safe limits of PEEK. Conclusions: Within the limitations of this study, bonding PEEK wires with 4 mm bonding spots to the clinical crown center provided the best mechanical performance of the wires and spots; otherwise, the mechanical properties of the wire and composite would be affected and, therefore, might affect the retention process. Keywords: Retention, PEEK, Finite element analysis